Metabolism of Urban Location: Travel Time and the Morphology of Cities - Braham, William W.; Lee, Jae Min (Frontiers in Sustainable Cities, 2020)
This paper examines the metabolism of urban location, which is offered as a contribution to the expansion of urban metabolism analysis beyond the largely biophysical methods of mass-energy-balance and emergy accounting. But how does the real estate logic of location enter the stock and flow calculations of urban metabolism, and how can it help us better understand the physiology of a more sustainable city? A new, locational quantity, EL, is defined as the additional emergy value obtained by a tract of urban land due to interconnection with the other land parcels in the city. It is based on their level of development and proximity measured in terms of travel time. The article uses the greater Philadelphia region as a case study to examine the metabolic value of location, and its role in the transition to a renewable economy.